2020
DOI: 10.1002/pd.5663
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of the septum pellucidum: Prenatal diagnosis and outcome

Abstract: Objective: The purpose of this study is to describe the imaging findings in a group of fetuses with suspected agenesis of the septum pellucidum (ASP) and to evaluate their clinical outcome.Methods: This is a retrospective multicenter study on a cohort of fetuses diagnosed with suspected ASP, between 2008 and 2017. The records of each patient, including ultrasound (US) and magnetic resonance studies, were reviewed and compared with the postnatal findings.Results: Forty-seven patients were included in the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 16 publications
2
19
2
7
Order By: Relevance
“…ASP is not typically seen as an isolated finding. Borkowski‐Tillman et al found that ASP can occur isolated or in combination with other developmental abnormalities such as corpus callosum agenesis, schizencephaly, holoprosencephaly, and ventriculomegaly [ 2 ]. Isolated ASP is associated with a favorable outcome but that ASP associated with other central nervous system findings can predispose to a high risk of abnormal neurodevelopment [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ASP is not typically seen as an isolated finding. Borkowski‐Tillman et al found that ASP can occur isolated or in combination with other developmental abnormalities such as corpus callosum agenesis, schizencephaly, holoprosencephaly, and ventriculomegaly [ 2 ]. Isolated ASP is associated with a favorable outcome but that ASP associated with other central nervous system findings can predispose to a high risk of abnormal neurodevelopment [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Borkowski‐Tillman et al found that ASP can occur isolated or in combination with other developmental abnormalities such as corpus callosum agenesis, schizencephaly, holoprosencephaly, and ventriculomegaly [ 2 ]. Isolated ASP is associated with a favorable outcome but that ASP associated with other central nervous system findings can predispose to a high risk of abnormal neurodevelopment [ 2 ]. Secondary, or acquired, causes of ASP are frequently due to long-standing hydrocephalus secondary to leptomeningitis, trauma, and porencephaly [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have demonstrated evidence that optic tract diameter increases linearly throughout gestation and provided reference ranges 9,12 ; in these two studies, a total of 14 fetuses were diagnosed with isolated ASP based on US examination of the optic pathways. Among these cases, all nine children from the series of Bault et al 9 had good ophthalmological outcome with normal vision, while all five children from the series of Vi ñals et al 12 17 Bault (2011) 9 Shinar (2020) 20 Borkowski-Tillman (2020) 21 Present study (2022) Combined 0.19 (0.04-0.46) 0.00 (0.00-0.37) 0.38 (0.09-0.76) 0.00 (0.00-0.23) 0.00 (0.00-0.23) 0.09 (0.01-0.24)…”
Section: Summary Of Evidencementioning
confidence: 97%
“…Esta evaluación cualitativa rápida aporta importante información sobre la existencia de al menos una porción del cuerpo calloso, y la simetría del sistema ventricular y de la zona periventricular, que puede ser asiento de patología del desarrollo cortical, hemorrágica o infecciosa (18,19) . Todo esto lo posiciona como una herramienta con potencial para la detección de holoprosencefalia (20,21) , anomalías comisurales (agenesia completa del cuerpo calloso, displasia septo-preóptica) (22)(23)(24)(25)(26)(27)(28) , esquisencefalia (29) y barotrauma (ventriculomegalia obstructiva) (30,31) .…”
Section: Evaluación Del 'Complejo Anterior'unclassified